The Self-Proclaimed Defender of Freedom: The AfD and the Pandemic - Pola Lehmann; Lisa Zehnter (Government and Opposition, 2022)
The COVID-19 pandemic has challenged nearly every aspect of life and superseded issues at the core of populist radical right (PRR) parties' ideology, dispossessing them of one of their main narratives. This also challenged the Alternative for Germany (AfD), a relatively young but strong PRR party in opposition. We explore how the party has adjusted its policy supply to this unprecedented situation and how this has affected its popularity among German voters, building our analysis on press releases issued by the AfD between January 2020 and March 2021, vote intention data and recent election results. Initially, the party's reaction was inconsistent, but from autumn 2020 the AfD focused on fuelling discontent with the government's lockdown measures, acting as a supporter of the anti-coronavirus demonstrations. It framed its response as elite critique. So far, its siding with the lockdown protesters, however, has not had any positive effect on support for the party.
Keywords: 300; COVID-19; populism; political parties; press releases; AfD